Estudo metaloproteômico do mércurio em amostras de tecido hepático de peixes coletados na área de influência do AHE JIRAU - Bacia do rio Madeira - Vieira, José Cavalcante Souza [UNESP] (2014)
In this dissertation work , we sought to evaluate and quantify the amount of mercury present in samples of fish jaraqui , tucunaré and filhote from the influence area of the AHE JIRAU - the Madeira basin , aiming to define a protein biomarker (metalloproteins, metallothionein) for monitoring this toxic metals in the environment. For this research, we used techniques of proteomics: two-dimensional electrophoresis (2D-PAGE), mass spectrometry. atomic absorption spectrometry and bioinformatics. With the atomic absorption analysis was possible to analize and quantify the mercury in protein spots obtained from the 2D-PAGE of protein and pellets of greater molar mass and smaller than 50 kDa. The characterization of the proteins were performed by mass spectrometry (ESI-MS), and thus being able to make a correlation between mercury in spots and proteins found in them. With these results, we can define a profile of protein biomarker for mercury in the applied samples. The selection of spots for this study was based on literature reports claiming affinity of mercury for proteins of low molecular weight and the measurements of mercury made by graphite furnace atomic absorption spectrometry (GFAAS), since the pellets with molar mass greater than 50 was not found mercury. Utilizing the GFASS requirements, the spots which their molecular mass were less than 20 kDa contained mercury concentration in the range of 11.30 to 88.40 mg g-1. Presented mercury in spots quantified by the atomic absorption spectrometry method. From 24 ESI-MS characterized spots, were identified 17 proteins, which may be used as biomarkers of this metal in the aquatic environment